Relationship between plasma cyclin-dependent kinase 5 levels and local immunoglobulin levels in patients with nasal polyps - Liu, Cui; Luo, Qian; Tang, Yan; Yu, Gaoxin; Liang, Kuai; Huang, Ligao (Cellular and Molecular Biology, 2021)
Nasal polyps are the most common benign nasal tumors that can lead to nasal obstruction and other annoying problems for the patient. Several hypotheses have been proposed as the basic mechanism of nasal polyps. In order to investigate one of the possible causes that can be a disorder in the regulation of systemic immune responses, the present study was designed to investigate the relationship between plasma cyclin-dependent kinase 5 (CDK5) levels and local immunoglobulin levels in patients with nasal polyps. A cross-section study was used to evaluate concentrations of local immunoglobulin levels (IgE, IgM, IgA, and IgG) on blood and polyp specimens from 60 patients with nasal polyps, and 60 control groups. Western Blot Analysis was done for CDK5 in plasma cells. IgA, IgG and IgE concentrations were significantly higher in polyp tissue specimens, but not in blood, of nasal polyp patients compared to the control group. Furthermore, plasma CDK5 levels were significantly higher in nasal polyp tissue compared with control. The difference in IgA, IgE and IgG expression between nasal polyp tissue and blood, supported by increased numbers of plasma cells, suggests a local production of these local immunoglobulins in nasal polyps in response to chronic antigens. Among local immunoglobulins, only there was a significant correlation between CDK5 with IgG (positive correlation) and IgE (negative correlation). The exact explanation for the relationship between plasma CDK5 and local immunoglobulins in nasal polyps needs further studies.